Membangun Sistem Smart Trash Menggunakan Mikrokontroler Motor Servo Panjerino - Hirmawan, Yuda; Riyanto, Eko; Solikhin, Solikhin (Jurnal Informatika UPGRIS, 2023)
To cultivate good behavior and care for the environment, SD Negeri 2 KuwasenJepara promotes proper waste disposal, but in reality, there are still many students who don't do it. The purpose of this research is to build a smart trash can to socialize waste disposal in an attractive way for students. We use a manual trash can that is integrated with the Arduino Uno. This smart trash system is able to open automatically when it detects movement within 50 cm and vice versa, and can emit a "Thank you for not littering" sound. The performance test results show that the ultrasonic sensor device opens and closes within 3.07 seconds at a distance of 15 centimeters and 3.06 seconds at a distance of 30 centimeters. The feasibility test of the tool obtained a score of â‰¥76% and an ease of use score of 87.7%.